PENYEBARAN HAMA KUTU PUTIH PEPAYA PARACOCCUS MARGINATUS WILLIAMS & GRANARA DE WILLINK (HEMIPTERA : PSEUDOCOCCIDAE) PADA BERBAGAI TANAMAN INANG DI KABUPATEN ENDE - Puu, Yustina Maria Silvia Wonga (Agriculture Faculty of Flores University, 2010)
Papaya is one of the many horticultural commodities grown by farmers. In mid-2008, thousands of trees in the District Sukaraga papaya, Bogor Regency pest infestation papaya white and whole tree has been attacked. P. marginatus is a prolific insect that attack several host plants, including tropical fruit crops and ornamental plants. This research aims to determine the spread of lice infestation in White Paracoccus marginatus Ende and type of host plants are attacked by pest Mite White Paracoccus marginatus. This study is useful to obtain information about the spread of pest P. marginatus in the district of Ende as a step in taking control measures, information to relevant agencies and farmer about the existence pf pest P. marginatus in Ende district, and continued research on the existence of natural enemies and pest bioecology O. Marginatus. Sampling study conducted in 21 sub-district in NTT Propinsis Ende. The study was conducted from March-August 2011. Materials used in this study plant pest Paracoccus marginatus, Alcohol 95%. The tools used are a collection of bottles, brushes, a microscope, transparent plastic, paper labels, Thermo-Hygrometer, coo box, stationery and literature. The result showe that the spread of pest P. marginatus was observed in 21 sub-district in Ende found only in the District 2 District East Ende and Ndona. Papaya is attacked by P. marginatus have chlorotic leaves, young leaves to fall and prospective fruits and fruit and leaves are covered by this pest by stacking layers of wax until the drought ends up dead. The intensity of damage caused by pest P. marginatus in the District of East Ende of 33.33% and 16.67% for Ndona District. The spread of pest P. marginatus in the district of Ende found at two locations namely Ende District East and District Ndona. Types of host plants are attacked by pest P. marginatus is Papaya plants.